Language development in children of 3, 4 and 5 years of age and the influence of family, social and educational environments - Baylón Mendoza, Miriam Rosa (2023)
Language development is progressive and starts from the first years of life. The fullness of the development of linguistic abilities, at the level of expression, comprehension and use of language, will depend on the genetic bases of each child and on the communicative interaction at home and in different environments. It is important to identify the most relevant aspects during the developmental period of language in order to prevent and timely address situations that could interfere with the development of language skills in children. Considering Noam Chomsky’s proposal, the child achieves the acquisition of the mother tongue through a cognitive process that allows the development of linguistic competence. After going through intermediate states and receiving linguistic stimuli in a community, the child internalizes the grammar of the language of his community, reaches a stable state and, consequently, will be able to produce and understand linguistic messages. The objective of this article is to base the process of acquisition of linguistic skills, analyze and contrast the influence of family, educational and social environments during the process of language development. For this, the application of a self-administered survey to 110 parents of children of 3, 4 and 5 years of age has been considered, in order to obtain information that allows knowing some aspects in relation to coexistence in family, social and educational environments with their minor children, and to establish the influence on the language development process.